Gender Based Comparison Gross Motor Skills and Physical Fitness Islamic and Public Elementary Students - Herawati, Yunia; Gumilang, Eva Sri (Sportify Journal, 2026)
Elementary students’ gross motor skills and physical fitness are important indicators of physical development, yet these outcomes may vary according to school context and gender-related movement opportunities. This study aimed to analyze differences in gross motor skills and physical fitness between students from Islamic-based elementary schools and public elementary schools based on gender. A quantitative comparative approach was employed. The sample consisted of 240 fourth-grade students from six elementary schools in Parongpong District, West Bandung Regency, selected using a two-stage cluster sampling technique. Gross motor skills were measured using the Test of Gross Motor Development 2, while physical fitness was measured using the Indonesian Physical Fitness Test Phase B. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene’s homogeneity test, and independent samples t-test. The findings showed that public elementary school students obtained higher mean scores in gross motor skills than Islamic-based elementary school students, with mean scores of 24.45 and 23.76, respectively. Physical fitness also showed a similar pattern, with public schools obtaining a mean score of 20.38 and Islamic-based schools obtaining 18.35. Hypothesis testing confirmed significant differences in gross motor skills, t (78) = 3.342, p = 0.001, and physical fitness, t (78) = 7.598, p < 0.001. Gender-based comparisons also showed significant differences among male and female students. These findings indicate that school context and gender should be considered in designing adaptive and inclusive physical education programs to optimize students’ physical development.